PENGARUH PENGUMUMAN KOMPONEN ARUS KAS, KEPUTUSAN PENDANAAN DAN RISIKO KESULITAN KEUANGAN TERHADAP RETURN SAHAM DENGAN MODERASI ROA (Studi Empiris pada Perusahaan Sektor Ritel yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Athira Salsabila; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2023)
This study was conducted to examine and analyze the effect of components of cash flow, funding decisions, and the risk of financial distress on stock returns with ROA moderation. This research was conducted on retail companies listed on the Indonesia Stock Exchange in the 2017-2020 period. The population in this study amounted to 20 companies. The sample selection used purposive sampling technique and obtained a sample of 15 companies, but there were outlier data so that the researchers deleted 4 companies, so that the total sample was 11 companies with a research period of 4 years so that 44 research data were obtained. This study uses the Eviews version 10 program to process the data. The hypothesis was tested using a panel data regression model with the Random Effects Model approach and testing the moderating variables using the Moderated Regression Analysis model. The results of this study indicate that the components of cash flow and funding decisions have no significant effect on stock returns, while the risk of financial distress has a negative effect on stock returns. In addition, the effect of cash flow components and funding decisions on stock returns cannot be moderated by the ROA variable, but ROA is able to moderate the effect of the risk of financial distress on stock returns.